Odnos reševalcev do uporabe različnih oblik prisilnih ukrepov - Muminović, Samir (Obzornik zdravstvene nege, 2017)
Introduction: Coercive measures are often used in prehospital environments. The purpose of the research was to determine their frequency and the attitudes of paramedics towards them. Methods: The questionnaire was completed by 178 paramedics. All segments of the questionnaire have shown suitable reliability (Cronbach alpha > 0.8). Data was represented with descriptive statistics, T test, ANOVA test and Pearson correlation with considering statistical significance (p < 00.5). Results: 165 paramedics (92.7 %) have been involved in coercive measure interventions. Women paramedics feel less safe than men (t = 3.243, p = 0.03) and are more supportive of police intervention (t = -0.572, p = 0.03). The most used coercive measure is restraining with police handcuffs (x = 3.30, s = 1.15). Aggression of patients directed at others (x = 4.22, s = 0.86), aggression directed at themselves (x = 4.23, s = 0.76) and agitation (x = 3.23, s = 0.98) are seen as the most justifiable causes for the use of coercive measures. Paramedics believe that they need more knowledge about this subject (x = 3.90, s = 1.01). Discussion and conclusion: Paramedics mention similar reasons for using coercive measures to the ones mentioned by hospital employees in previous research. However, the opinion of the paramedics about using these measures is negative and they only agree with using coercive measures in the case of patients with aggressive behaviour. They feel endangered at their job. They need training and education on the use of coercive measures.
Keywords: emergency unit; medicinske sestre; nursing; posebni varovalni ukrepi; prisilni jopič; special coercive measures; straitjacket; urgenca